Anthropometric Indices And Mental Health Of Workers In Health Sector In Saltillo Mexico - Nupo, Sunday Sedodo; Martinez Martinez , Viridiana; Ortiz-Cruz, Gabriela; Cortés-Hernandéz, Jose Lauro; Aguilar, Cristobal Noe; Sandoval-Cortés , Jose (Journal of Basic and Applied Psychology Research, 2026)
Mental health problems are increasingly common and disabling in México, particularly among healthcare workers. This study aimed to estimate the prevalence of depression, anxiety, and stress, and to examine associations between anthropometric indices and psychological outcomes in healthcare workers in Saltillo, Mexico. A cross-sectional study was conducted with 258 healthcare workers from University Hospital of the Autonomous University of Coahuila. Sociodemographic and lifestyle data were collected using a validated questionnaire. Anthropometric measures (weight, height, mid- upper arm circumference, waist and hip circumferences) were obtained using standardized procedures. Mental health status was assessed with the Depression, Anxiety, Stress Scale (DASS-42). Multiple linear regression models were applied to explore associations, reporting regression coefficients (B), 95% confidence intervals, p-values, and R2. Depression, anxiety, and stress (ranging from mild to extremely severe) were present in 51.2%, 31.8%, and 25.2% of participants, respectively. Overweight and obesity were frequent, with 21.3% and 17.1% classified as grade I and II obesity. Regression analyses showed limited explanatory power of anthropometric indices (R2 = 0.60-0.66). BMI and waist circumference were significantly associated with anxiety and stress, while alcohol consumption and smoking were more consistently related to depression and anxiety. High levels of depression and obesity were observed, but anthropometric indices explained only a modest proportion of psychological outcomes. Psychosocial and lifestyle factors appear more decisive. Preventive interventions should integrate physical health promotion with psychological support, and future longitudinal studies are needed to clarify causal pathways.